Development of a model for the disposal of space debris during combustion in the atmosphere - O. G. Feoktistova; I. I. Turkina (Научный вестник МГТУ ГА, 2022)
Due to the increasing use of outer space, the issue of space debris disposal (SD) is becoming an urgent problem. Of the known disposal methods (using a solar sail, atmospheric resistance, electrodynamic cable system, laser, ion flow, gravitational cleaner, contact method), the article focuses on the method of burning up space debris in the Earth’s atmosphere by engaging it with a special device for collecting SD and impulse emitting by a debris collector to deorbit with certain parameters. Based on the methodologies of computing the trajectories of the object descent via the extra-atmospheric and atmospheric areas, as well as heat calculation, a mathematical model was developed in the Mathcad system to calculate the timespan required for the complete destruction of SD in the Earth's atmosphere. A comparative analysis was carried out on the accumulated heat flux, as well as on the duration and altitude at which SD, containing aluminum or refractory metals such as titanium and tungsten, will burn up. The altitudes optimal for burning up SD were determined and evaluated. They are acceptable according to the criterion of public safety. The conducted computational experiment revealed that SD made of an aluminum alloy weighing 10 kg burns up at an altitude of 94.9 km, a 17 kg titanium piece burns at an altitude of 94.7 km, a 73 kg tungsten piece does at an altitude of 97.7 km. Thus, this model allows us to classify the existing SD objects into those that can burn up in the atmosphere before reaching a given altitude (not reaching the Earth’s surface), and those that require the employment of other methods to clean space from debris.